An application system for the design of the spindle tool clamping mechanism - Ragul Ramanathan; Parthiban Kannan (International Journal of Advances in Applied Sciences, 2021)
The heart of the machining center design is the spindle design, and one of the primary functions in the spindle design is a tool clamping system mechanism. The selection of disc spring stack for a tool clamping mechanism is an iterative process that highly depends on the spindle space availability, drawbar design, tool unclamp stroke length, and standard clamping force requirements. For example, even a design space of 0.1 mm may impact one kN clamping force depending on the disc spring stack design. Hence the design of the tool clamping system for a spindle is a time-intensive process and also needed careful attention. The iterative process of disc spring stack selection may lead to an unoptimized tool clamping system, which may not be the best design. This paper explains a dynamic way to find the best spring stack selection to optimize the spindle tool clamping mechanism based on the computational application.